Τhe Digistoryteller project: walking around refugee Attica - Antoniou, Angeliki; Chrysanthopoulos, Christos; Efthymiou, Foteini; Papastathis, Konstantinos; Theodosis, Stathis; Kamara, Afroditi; Triantafyllou, Ioannis (Journal of Integrated Information Management, 2024)
Purpose - The present work focuses on an app that supports historical exploration of city neighborhoods. The particular work focuses on the refugee crisis resulting from the Greco-Turkish war in 1922 and the traces it left behind in the formations of different places across Attica. To present the past, we developed digital storytelling features, and to engage users further, we provided them with crowdsourcing functionalities allowing them to create their own content. Design/methodology/approach - The digital storytelling and the crowdsourcing features were tested with users in multiple events, using a mixed methodology that allowed the collection of qualitative and quantitative data from the public, policy makers and experts. Findings - Most users provided very positive feedback and imagined further educational uses. Originality/value - The different features of this mobile approach, allow an in-depth engagement with the past while the user is mobile.